DOCTORS’ ATTITUDE TOWARDS THEIR PSYCHOLOGICAL COMPETENCES AS A COMPONENT OF PROFESSIONAL SELF-REFLECTION - A. G. Shevtsov; O. L. Zyukov; O. O. Oshivalova (Клінічна та профілактична медицина, 2023)
The purpose of the research is to study doctors’ attitude towards the role of psychological competencies in their professional activities and its assessment as well as to investigate doctors’ self-assessment of their psychological knowledge, skills and abilities to demonstrate various forms of communication with certain groups of patients as an important component of professional reflection. Participating in the research doctors were different specialty experts of different age groups and experience, employed in multidisciplinary health care institutions.